Community mental health teams for older people in England: Variations in ways of working. (23rd August 2017) - Verbeek, Hilde; Worden, Angela; Wilberforce, Mark; Brand, Christian; Tucker, Sue; Abendstern, Michele; Challis, David
Abstract : Objective: Integrated community mental health teams (CMHTs) are a key component of specialist old age psychiatry services internationally. However, in England, significant shifts in policy, including a focus on dementia and age inclusive services, have influenced provision. This study portrays teams in 2009 against which subsequent service provision may be compared. Methods: A bespoke national postal survey of CMHT managers collected data on teams' structure, composition, organisation, working practices, case management, and liaison activities. Results: A total of 376 CMHTs (88%) responded. Teams comprised a widespread of disciplines. However, just 28% contained the full complement of professionals recommended by government policy. Over 93% of teams had a single point of access, but some GPs bypassed this, and 40% of teams did not accept direct referrals from care homes. Initial assessments were undertaken by multiple disciplines, and 71% of teams used common assessment documentation. Nevertheless, many social workers maintained both NHS and local authority records. In 92% of teams, nominated care coordinators oversaw the support provided by other team members. However, inter‐agency care coordination was less prevalent. Few teams offered the range of outreach/liaison activities anticipated in the national dementia strategy. Conclusions: Compared with previous studies, teams had grown and changed, with a clear increase in non‐medical practitioners, particularly support workers. Measures to facilitate integrated care within CMHTs (eg, common access and documentation) were widespread, but integration across health and social care/primary and secondary services was less developed. Consideration of barriers to further integration, and the impact of current reforms is potentially fruitful.